Cultural patterns of the popular Mawlidiya of Tlemcen (مجلة إحالات, 2026)
The celebration of the Prophet's birthday (Mawlid al-Nabawi) is one of the significant occasions in theArab and Islamic worlds. Over the ages, the forms of this celebration have evolved, adopting variouscustoms and rituals that differ from one community to another. It took on an official form in Tlemcen during the era of the Zayyanid dynasty, where religious celebrations were utilized as a means to strengthen theauthority of the sultans and unify Muslims under the banner of the state.The sultans relied on religious celebrations to reinforce the bonds between the ruler and the subjects. This tradition is considered a manifestation of religious presence in the Islamic imagination of the people of Tlemcen, keeping it alive in their daily lives and establishing it as an official tradition that strengthens the bonds of unity among members of the Zayyanid society in Tlemcen. This was especially evident during thereigns of Yaghmurasen Ibn Zayyan and Abu Hammu Musa II.